Conductive Fabric Study and Its Application for Wearable Devices - Noor Azam, Luqman; S. H. Dahlan (Journal of Electronic Voltage and Application, 2026)
The integration of electronics into clothes has created demand for aesthetic, flexible and conductive materials that can serve as reliable circuit paths. Among these, conductive fabrics have emerged as a promising alternative to conventional wires in wearable devices due to their lightweight structure, comfort and ability to follow the movement. This study investigates the performance of a silver-plated nylon fabric, MedTex130 as a conductive fabric in a simple wearable LED circuit application. A series of experimental tests were conducted to evaluate the fabric’s electrical behaviour under real-world conditions. Resistance was measured across various strip lengths 1?cm to 8?cm, widths 0.3?cm on shiny and non-shiny surfaces. Additional tests evaluated how stretching up to 100% affected resistance value, how the fabric responded to 0Hz frequency direct current (DC) voltage up to 12?V and how thermal stress from soldering impacted conductivity and material integrity. The results showed that resistance increased with length and decreased with width, consistent with Ohm’s law. Interestingly, resistance dropped significantly when the fabric was stretched, particularly on the non-shiny side, with some samples showing up to 94% reduction. Although the fabric supported LED activation up to 12?V, significant heat build-up was observed above 5?V. Furthermore, soldering at typical temperatures ?350°C caused permanent damage to the silver coating, leading to a drastic increase in resistance. The observed resistance variation and thermal degradation directly affect power efficiency, user safety and long-term reliability in wearable devices, indicating that conductive fabrics are suitable only for low-voltage, low-current applications with careful thermal management. Overall, the findings confirm the fabric’s capability for low-voltage wearable circuits but also highlight limitations in heat tolerance and the need for alternative joining methods.